Correlated disorder in metal–organic frameworks. Issue 16 (10th March 2021) - Meekel, Emily G.; Goodwin, Andrew L.
Abstract : Metal–organic frameworks host many types of compositional and structural disorder. In this Highlight article we explore cases where this disorder is correlated, rather than random. Abstract : We survey the importance of correlated—as opposed to random—disorder in metal–organic frameworks (MOFs), focussing on correlations in vacancy arrangements, composition, and linker orientations in some canonical systems. We explore the link to physical and chemical properties, and highlight the various experimental and computational tools available for characterising and interpreting correlated disorder in MOFs.